Effect of amine compound-post treatments on formaldehyde emission and properties of urea formaldehyde (UF) - bonded particleboard - Muhammad, Nurul Izfahani (2017)
One of the drawbacks of using urea formaldehyde bonded particleboard is the formaldehyde emission. There are many attempts in reducing the FE from urea formaldehyde bonded particleboard by modifying the urea and formaldehyde formulation but this system would give a negative impact to the performance of the board. The aim of this study was to determine the effect of amine compound-post treatment on formaldehyde emission and properties of UF-bonded particleboard. UF-bonded particleboard was treated with solution of amine compounds at different rates of spread on the surfaces of the boards. The results show that spreading of at 20 g/m² propylamine can reduce FE to below 0.4 mg/L and this system surpassed the standard F*** limit which is < 0.5 mg/L. Ethylamine and methylamine with a spread rate of 20 – 60 g/m² were also found to reduce FE and the FE was lower than the untreated particleboard. It was also found that this treatment system did not significantly affect physical and mechanical properties of the particleboard.